From absorption capacity to in-company knowledge generation: key aspects’ identification - Ponce-Espinosa, Glenda (2020)
The ability of organizations to absorb knowledge from the external environment is a topic that has gained great attention in recent years, both from a theoretical and a practical perspective. However, the identification of the factors that precede this phenomenon in organizations, the moderating role, and the effects of absorptive capacity in the organization still remain in a field of research scarcely explored. Given the importance of the subject, the main objective of this work is to identify the determining factors of the absorptive capacity. In this paper, the citations’ analysis is combined with the systematic review of the literature approach. The different factors that have an impact on the absorption capacity are identified, and are classified as antecedents, determinants, and components of the absorption capacity. These factors are associated with knowledge, organizational elements, and staff behavior, among others. From the different contributions until 2016, literature uncovered gaps are identified, that may guide future research and influence the understanding of absorption capacity in organizations.